Preventive regulation of autonomous weapon systems: Need for action by Germany at various levels - Anja Dahlmann; Marcel Dickow (Stiftung Wissenschaft und Politik (SWP), 2019)
The authors argue that in order for Germany to do justice to its claim of outlawing lethal autonomous weapon systems (LAWS) internationally, the Federal Government should first define the term 'human control', for example in a strategic document from the Federal Ministry of Defence. The aim should be to facilitate the regulation of the development and use of LAWS - at the international level - thus making the issue of military robotics politically manageable. The international framework for negotiating the regulation of LAWS is currently the United Nations Convention on Certain Conventional Weapons. A Common Position of the EU member states that demands human control - or, better still, suggests proposals for its design - could have a decisive influence on the negotiations.
Keywords: 320